2011
DOI: 10.1111/j.1365-2427.2010.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of risk and disease modelling to emerging freshwater diseases in wild aquatic animals

Abstract: Summary 1. Emerging diseases pose significant ecological and economic threats in fresh waters. Both risk assessment and mathematical modelling have potential to improve our understanding of the uncertainties associated with emerging disease events and make informed predictions about their likely impact. 2. We review the different methodologies that may be used to estimate the likely geographic spread and potential impact of new and emerging diseases in fresh waters. We also highlight the limitations of the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 115 publications
(177 reference statements)
0
25
0
Order By: Relevance
“…In aquaculture systems, confinement stress such as high densities of rearing fishes is more likely to weaken the immune systems, resulting in vulnerability to pathogen infections (Portz, Woodley, & Cech, ). Thrush, Murray, Brun, Wallace, and Peeler () also revealed that high host density, poor environment and intercurrent disease (occurring during the course of another disease) undermined immunity in farmed stocks and reduced resistance to diseases while enhancing contact frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture systems, confinement stress such as high densities of rearing fishes is more likely to weaken the immune systems, resulting in vulnerability to pathogen infections (Portz, Woodley, & Cech, ). Thrush, Murray, Brun, Wallace, and Peeler () also revealed that high host density, poor environment and intercurrent disease (occurring during the course of another disease) undermined immunity in farmed stocks and reduced resistance to diseases while enhancing contact frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, it may be more realistic to aim for mitigation and management of EIDs and invasions guided by robust risk assessment on a case鈥恇y鈥恈ase basis (Thrush et al . ). We thus encourage those engaged in EID and invasion research to facilitate this with further cross鈥恌ostering of ideas and approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Tatem, Hay & Rogers ; see also Thrush et al . for risk assessment models applied to aquatic EIDs). Some papers recognize structural similarities between invasions and emergence; for instance, Chades et al .…”
Section: Discussionmentioning
confidence: 99%
“…Also, recently it has shown the potential of surveillance systems based on risk for early detection of emerging diseases in aquaculture through the development of epidemiological models (Thrush et al . ).…”
Section: Introductionmentioning
confidence: 97%